Biodiversity on oceanic islands: evolutionary records of past migration events - Wink, Michael (Heidelberger Jahrbücher online, 2018)
Oceanic islands are mostly of volcanic origin. Most of them harbour a diverse fauna and flora, which had not been there before. All plants and animals must have reached the islands by sea or wind or through human activities. Thus, all these island taxa are witnesses of migration events in the past and are models for biogeography. In this review, fauna (especially birds) and flora of the Macaronesian islands west of Europe and North Africa in the Atlantic are discussed. The Macaronesian islands comprise 4 archipelagos with 31 main islands, including the Azores, Madeira, Canary Islands and Cape Verde Islands. These islands are of volcanic origin and between 120 and < 1 million years old. Flora and fauna mostly consist of species, that originally originated from Europe or Africa and arrived within the last 4 million years. More than 23% of the terrestrial taxa are endemic to the area. Genetic analyses have confirmed most of the morphologically defined endemic species and subspecies. In some species groups, a strong speciation signal becomes visible in that distinct genetic lineages occur on individual islands or archipelagos. This is especially apparent in Phylloscopus canariensis, Regulus regulus, Cyanistes [caeruleus] teneriffae, Erithacus rubecula, and Fringilla coelebs. The diversity of the Macaronesian islands offers an excellent opportunity to study adaptive radiation and speciation in organisms of differing complexity and mobility.